Study of Vulnerability Diagnosis and Sustaining Integrity of the Embedded Devices - Fujikawa, Masaki (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Security vulnerability of the embedded devices with Internet connectivity is frequently reported these days. In this paper, a diagnosis was made for a security vulnerability in the controller that is an element of the security system installed in homes and offices and connected to the Internet. The results showed a part of the functions of the controller may be suspended and the integrity of the security system may be lost due to an attack of known malware. In the latter part of this paper, the possible impacts on the controller and the security system were predicted based on the attack scenario on the security system initiated by the attack on the controller. It was also discussed what requirements must be fulfilled by the controller and the security system and about the need for a diagnosis for an unknown vulnerability.